Evaluation of the accuracy in detecting cervical lesions by nurses versus doctors using a stationary colposcope and Gynocular in a low-resource setting. Issue 11 (3rd November 2014) - Nessa, Ashrafun; Roy, Joya Shree; Chowdhury, Most Afroza; Khanam, Quayuma; Afroz, Romena; Wistrand, Charlotte; Thuresson, Marcus; Thorsell, Malin; Shemer, Isaac; Wikström Shemer, Elisabeth Andrea
Abstract : Objectives: Evaluation of the performance of VIA (visual inspection with acetic acid) trained nurses to learn colposcopy and the Swede score method to detect cervical lesions by using stationary colposcope or a portable, hand-held colposcope; the Gynocular, as compared to doctors. Design: A crossover randomised clinical trial. Setting: The Colposcopy Clinic of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh. Participants: 932 women attending the clinic as either screening naïve for VIA screening (404) or women referred as VIA positive (528) from other VIA screening centres in the Dhaka region. Intervention: VIA trained nurses were trained on-site in colposcopy and in the Swede score systematic colposcopy method. The Swede score grade cervical acetowhiteness, margins plus surface. vessel pattern, lesion size and iodine staining. The women were randomised to start the examination by either a stationary colposcope or the Gynocular. Swede scores were first obtained by a nurse and the same patient was equally evaluated by a doctor. Primary and secondary outcome measures: Agreement between nurses and doctors in Swede scores was evaluated using the weighted κ statistic for the Gynocular and standard colposcope. The ability to predict CIN 2+ (CIN 2, CIN 3 and invasive cervical cancer) using Swede scores was evaluated using receiver-operating characteristic curves. Results: The Swede scores obtained by nurses and doctors using the Gynocular and stationary colposcope showed high agreement with a κ statistic of 0.858 and 0.859, respectively, and no difference in detecting cervical lesions in biopsy. Biopsy detected CIN 2+ in 39 (4.2%) women. Conclusions: Our study showed that VIA nurses can perform colposcopy. There was no significant differences compared to doctors in detecting cervical lesions by stationary colposcope or the Gynocular using the Swede score system. Swede scores obtained by nurses using the Gynocular could offer an accurate cervical diagnostic approach in low resource settings. Trial registration number: ISRCTN53264564.